295 Evidence-based advocacy for safer transportation for factory workers in Cambodia. (20th November 2022) - Nguyen, Nhung; Nguyen, Le; Im, Piseth; Sidik, Mirjam
Abstract : Context: About 90% of workers in Cambodia commute daily by either truck or motorcycle, which makes nearly 700, 000 factory workers vulnerable to road traffic crashes. Process: A national advocacy campaign was designed to support the transition from trucks to safer worker transportation vehicles. Its goal is that the Cambodian government, brands, industrial zones, and factories will establish and implement policies and regulations that facilitate the transition. Major activities include: - A study that assesses existing and potential passenger transport options for factory workers. - A policy brief (PB) - Meetings and workshops to engage stakeholders and disseminate the study's findings Analysis: The study involved 511 transport operators (TOs) and 608 workers from twelve factories across seven provinces. 71% of surveyed workers travel to and from work by truck. Safer passenger vehicles, including vans, buses, and public buses, are reported to be available by respectively 36%, 27%, and 2% of workers. 90% of TOs reported using loans to purchase their vehicles, and 45% would be willing to change to safer vehicles if affordable. Outcomes: A PB was developed to provide recommendations, in which the current approach to modifying trucks should be short-term, while regulations on vehicle standards should be set and enforced long-term. Two national workshops with nearly 200 participants from various stakeholders were held in 2021 to share the study findings and gather inputs. Next Steps: The campaign's follow-up activities include submission of the PB and incorporating policy recommendations into agendas of upcoming meetings with concerned government bodies and stakeholders.